Grounding Animal Rights in Mutual Advantage Contractarianism - Taylor, Matthew (Les ateliers de l'éthique / The Ethics Forum, 2014)
Contrary to critics and advocates of contractarianism alike, I argue that mutual advantage contractarianism entails rights and protections for animals. In section one I outline the criteria that must be met in order for an individual to qualify for moral rights on the contractarian view. I then introduce an alternative form of ‘rights,’ which I call ‘protectorate status,’ from which an individual can receive protections indirectly. In section two I suggest guidelines for assigning animal rights based on two ways of categorizing animals. On the basis of the categorization according to benefit derived, I argue that animals used for companionship, security, hunting assistance, transportation, entertainment, medical service, nourishment, or clothing will tend to qualify for basic rights against starvation, predation, and disease. On the basis of the categorization according to species, I argue that, on top of the basic rights above, dogs tend to qualify for rights against abuse, and against frivolous medical experimentation, as well as further negotiated rights. Cows have the basic rights against starvation, predation, and disease, but squirrels and bears have no rights. In section three I argue that some animals qualify for protectorate status, which would establish various protections for different animals, but would also generally prohibit cruelty towards animals.